Ilhas do sistema hídrico Guamá-Guajará caracterização sócio-ambiental e propostas para desenvolvimento - MALCHER, Alessandra do Socorro Pinheiro (2018)
The islands present in the system Guamá-Guajará have serious socioeconomic difficulties that were the object of this work. The main objective was to consider the main difficulties encountered by the population of the islands and make specific proposals to redress these problems. Field work and responses to a questionnaire answered by about 10% of the population made it possible to analyze the socioeconomic profile of the population of two islands (and Combu Murutucum). It was possible to establish a set of proposals for the sustainable development of this important sector of the state of Pará, including the assembly of small water supply systems, using groundwater or rainwater. The use of fruit, fish and ecotourism specific projects are proposed to minimize barriers to employment and income levels.